An investigation into the challenges in the adoption of information communication and technology in a selected primary school in Warren Park - Mushinga, Nyarai (Midlands State University, 2019)
Lack of ICT resources has negatively impacted on the full and effective adoption of ICT in education as well as the implementation of the new curriculum in the Zimbabwean context. ICT was adopted in the primary schools but the level of adoption is still in its infancy stage due to mainly shortage of resources and facilitators who lack ICT skills. This study sought to dig deeper into the challenges that are hindering the effective adoption of ICT in the primary school. Questionnaire, Interviews and Observations were used for data collection in this research study. A sample of 41 participants was selected from a target population of 409 teachers and students. Selection of teachers was done using purposive sampling and students using random sampling. Mixed method paradigm was used and the research design employed was a case study. Data were analysed using frequencies and percentages. Findings revealed that effective ICT adoption is mainly hindered by shortage of ICT tools and lack of expertise. Recommendations were made to the Ministry of Primary and Secondary Education through the district do some follow ups in the primary schools in order to ensure that ICTs are being used in teaching and learning. The ministry can as well can facilitate the purchasing of ICT by engaging companies that sell ICT equipment so that the schools can procure them at favourable prices and conditions. The schools can also harness the adoption by adopting the tablet computers to use in classrooms. The recommendations would promote the effective and full of adoption and integration of ICTs in the primary schools.